Odor Classification using Agent Technology - Omatu, Sigeru; Wada, Tatsuyuki; Chamoso, Pablo (Advances in distributed computing and artificial intelligence journal, 2014)
In order to measure and classify odors, Quartz Crystal Microbalance (QCM) can be used. In the present study, seven QCM sensors and three different odors are used. The system has been developed as a virtual organization of agents using an agent platform called PANGEA (Platform for Automatic coNstruction of orGanizations of intElligent Agents). This is a platform for developing open multi-agent systems, specifically those including organizational aspects. The main reason for the use of agents is the scalability of the platform, i.e. the way in which it models the services. The system models functionalities as services inside the agents, or as Service Oriented Approach (SOA) architecture compliant services using Web Services. This way the adaptation of the odor classification systems with new algorithms, tools and classification techniques is allowed.